2022
DOI: 10.1057/s41269-022-00258-3
|View full text |Cite
|
Sign up to set email alerts
|

The delusive economy: how information and affect colour perceptions of national economic performance

Abstract: Economic knowledge plays a central role in many theories of political behavior. But empirical studies have found many citizens to be poorly informed about the official state of the economy. Analyzing two waves of the Eurobarometer database, we re-examine the distribution of public knowledge of three macroeconomic indicators in two dozen European countries. Respondents with high income and education give more accurate estimates than others, in line with previous studies. As we show, however, such differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, differences found in economic groups could be explained by the magnitude in which inflation and poverty influence the below-average group’s decision-making and the constraints it would create for earning a living. Likewise, this type of reasoning is consistent with the tendency to reflect one’s current situation in economic opinions and attitudes ( Linsi et al , 2022 ). Thus, it should be credible that members of the below-average group would worry more about inflation and poverty since they already have experienced difficulties coping with the current economy.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…On the other hand, differences found in economic groups could be explained by the magnitude in which inflation and poverty influence the below-average group’s decision-making and the constraints it would create for earning a living. Likewise, this type of reasoning is consistent with the tendency to reflect one’s current situation in economic opinions and attitudes ( Linsi et al , 2022 ). Thus, it should be credible that members of the below-average group would worry more about inflation and poverty since they already have experienced difficulties coping with the current economy.…”
Section: Discussionsupporting
confidence: 72%
“…Also, responses serve as an unorthodox measure of students’ economic knowledge if we consider how objective knowledge makes part of their judgment. Literature has reported that decision is not knowledge-based solely ( Linsi et al , 2022 ), we contribute to that statement since it is clear that a vast majority of economic topics were ignored by respondents even though the war has a major impact on them, which is to say that there are other aspects like socio-demographic characteristics or other unmeasured variables that condition their opinion. In addition, we offer some insights about how well respondents detect the economic consequences of war for their own country when the corresponding conflict affects markets and prices globally due to other circumstances, even though the respondents’ country does not participate directly in the conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation